THE RELATIONSHIP OF COMPLIANCE WITH MEDICATION ON BLOOD PRESSURE STABILITY IN HYPERTENSION PATIENTS AT CINERE DISTRICT HEALTH CENTER 2023 - Sumantri, Salsabila; rahmi, eldiza puji; Rifkia, Via; Pradana, Dhinga Luthfiyani (Journal of Research in Pharmacy and Pharmaceutical Sciences, 2023)
Several reasons for hypertension sufferers who do not comply with taking medication will slow down healing time and worsen the patient's condition and can even cause death. This study aims to determine the characteristics of hypertensive patients at the Cinere Community Health Center, the results of antihypertensive therapy at the Cinere Community Health Center and to determine the relationship between adherence to medication use and the success of therapy at the Cinere Community Health Center. This research uses a correlational analytical research design. Based on the discussion above, it can be concluded that the characteristics of hypertensive patients at the Cinere Community Health Center are the majority aged 45-65 years, female with the highest education level being elementary school and having suffered for > 1 year. The majority of medication adherence among hypertensive patients at the Cinere Community Health Center is still relatively low. The success of therapy in hypertensive patients at the Cinere Community Health Center resulted in a reduction in blood pressure of 31 people and in patients who did not reduce blood pressure there were 71 people. There is a relationship between adherence to taking medication and blood pressure stability in hypertensive patients at the Cinere Community Health Center